Retraction Note to: Excessive mitochondrial fragmentation triggered by erlotinib promotes pancreatic cancer PANC‑1 cell apoptosis via activating the mROS‑HtrA2/Omi pathways - Jun Wan; Jie Cui; Lei Wang; Kunpeng Wu; Xiaoping Hong; Yulin Zou; Shuang Zhao; Hong Ke (Cancer Cell International, 2019)
The authors have retracted this article [1] because Figure 4a has been duplicated from Figure 5d in a previously published article [2]. In addition, the article contains sections that substantially overlap with the following articles (amongst others) [3–5]. The data reported in this article are therefore unreliable. Author Hong Ke stated on behalf of all co-authors that they agree to this retraction.